DPP4 in Diabetes - Röhrborn, Diana; Wronkowitz, Nina; Eckel, Juergen (Frontiers in Immunology, 2015)
Dipeptidyl peptidase 4 (DPP4) is a glycoprotein of 110 kDa, which is ubiquitously expressed on the surface of a variety of cells. This exopeptidase selectively cleaves N-terminal dipeptides from a variety of substrates, including cytokines, growth factors neuropeptides, and the incretin hormones. Expression of DPP4 is substantially dysregulated in a variety of disease states including inflammation, cancer, obesity and diabetes. Since the incretin hormones GLP-1 and GIP are major regulators of post-prandial insulin secretion, inhibition of DPP4 by the gliptin family of drugs has gained considerable interest for the therapy of type 2 diabetic patients. In this review, we summarise the current knowledge on the DPP4 - incretin axis, and evaluate most recent findings on DPP4 inhibitors. Furthermore, DPP4 as a type II transmembrane protein is also known to be cleaved from the cell membrane involving different metalloproteases in a cell-type specific manner. Circulating, soluble DPP4 has been identified as a new adipokine which exerts both para- and endocrine effects. Recently, a novel receptor for soluble DPP4 has been identified and data are accumulating that the adipokine-related effects of DPP4 may play an important role in the pathogenesis of cardiovascular disease. Importantly, circulating DPP4 is augmented in obese and type 2 diabetic subjects and it may represent a molecular link between obesity and vascular dysfunction. A critical evaluation of the impact of circulating DPP4 is presented and the potential role of DPP4 inhibition at this level is also discussed.